REFORMING THE SOCIAL INSURANCE SYSTEM IN UKRAINE: PROBLEM ASPECTS AND KEY TASKS (World of finance, 2023)
Introduction. In modern conditions, Ukraine faced the issue of ensuring an adequate level of social protection of citizens against the background of their impoverishment and mass resettlement, as well as the rapid increase in prices and the number of those who lost their jobs and housing. Social insurance is an important component of the social protection system. It provides for the receipt by insured persons of various types of social benefits in the event of the occur rence of certain negative events caused by social risks. In this context, the question of increasing the effectiveness of the functioning of the social insurance system within the framework of the assessment of problematic aspects and key tasks of its further reform is brought up to date.The purpose of the article is a comprehensive analysis of the main principles of reforming the social insurance system in Ukraine in order to raise the standard of living of the population and protect it from new social upheavals and threats; identification of problematic aspects that accompany the specified changes; outlining promising directions for further improvement of the national social insurance system to ensure effective insurance protection and decent financial support for each insured person.Results. It has been established that social insurance is evidence of the sociality of any state that recognizes the supremacy of social values, cares for its citizens and adheres to declared social standards. It is argued that social challenges accompanying social transformations in the country, intensified by ATO, a pandemic and a full-scale war, necessitated the need for effective social security of citizens, the basis of which is social insurance itself. It is shown that the social insurance system has undergone many changes over the years of its existence. A critical analysis of the main reforms, which most affected the sphere of pension provision of the population and the health care system, reorganization of social insurance funds, was carried out. It has been proven that this transformation did not give the desired result, and social problems are only increasing. It is indicated that the important determinants of ensuring the effectiveness of the further reform of the social insurance system are: flexibility and adaptability of the system, its ability to adapt to the conditions of today; ensuring effective management of financial resources of social insurance funds, ensuring their non-deficit; systematic implementation of improvements and their compliance with international standards and social guarantees; deep awareness by employees and employers of the need to conduct labor activities honestly and openly.Conclusions. According to the results of the study, it was established that the main organizational and legal form of social security is social insurance within the framework of support and material stimulation of economically active citizens and improvement of the material situation of vulnerable population groups. The prospect of reforming the social insurance system in Ukraine depends on the effective cooperation of the state, employers and employees in the form of open dialogue and social responsibility of the parties to achieve the desired result – raising the level of social standards and high-quality social protection of citizens, intensification of labor activity and overcoming social upheavals.